Establishment and applications of specific nursing models for patients undergoing orthognathic surgery - LIU Fan, BAI Yuanyan (口腔疾病防治)
Dentofacial deformity is a disorder of the volume and morphological structure of the jaws and the positional relationship between the maxilla and mandible caused by abnormal development of the jaws, which is manifested by abnormal facial morphology, malocclusion and dysfunction of the stomatognathic system. Orthognathic surgery is an important means of treating dentofacial deformity, and the development of specialized nursing plans for orthognathic surgery needs to be developed based on the diagnostic and treatment characteristics and needs of different disease courses. This article proposed recommended nursing practices as a means of constructing a specialized nursing model for orthognathic surgery and providing standardized management for orthognathic patients throughout the entire cycle by reviewing previous literature and summarizing the nursing practice experience of our hospital in treating more than 3 000 patients undergoing orthognathic surgery and classify clinical nursing evidence according to the Oxford Evidence Grading Standards. The model is divided into three main phases: prehospital early referral care, in-hospital intensive care, and posthospital extended care, and contains five modules: case management, psychological intervention, nutritional guidance, management of complications, and functional recovery. In the pre-hospital early referral care stage, the specific nursing measures include digital surgical design, psychological care, and nutritional guidance; in the in-hospital cluster care stage, the specific nursing measures include four modules, such as management of complications, orofacial functional recovery, nutritional instructions, and psychological interventions; and in the post-hospital extended care stage, the patients need to be provided with case management, psychological guidance, nutritional guidance, and other nursing care. Post-hospital extended care stage, need to provide patients with case management, psychological guidance, nutritional guidance and other care.